ASSESSMENT OF THE RISK FACTORS CONTRIBUTING TO INCREASE CHOLELITHIASIS CASES IN PUNJAB: A CROSS SECTIONAL STUDY (The Research of Medical Science Review, 2024)
Background: Cholelithiasis is a pathological condition of the digestive system, characterized by the presence of stones originating in the gallbladder. Cholelithiasis is a prevalent medical condition worldwide. Recognizing high-risk populations and creating specialized preventative and intervention plans can be made easier by having a thorough understanding of the risk factors unique to a given area.Objective: To assess the risk factors contributing to increase cholelithiasis cases.Method: Descriptive cross-sectional study conducted in mayo hospital, Lahore. Convenience sampling technique was used to select the study participant. Data were collected from the study participants with help of questionnaire. The participants were recruited and written consent is obtained from each participant. The data is analyzed with the help of frequency and percentage.Results: The majority of participants were over 40 years old (60.9%), with 39.1% falling between 30 and 40 years. Most participants were female (82.8%), married (91.4%), literate (70.3%), and resided in urban areas (71.9%). A significant portion came from a low socioeconomic background, with 50.78% reporting monthly incomes below 30,000. Regarding health factors, 64.8% had no family history of cholelithiasis. Alcohol consumption was reported by 5.5%, while 8.6% were active smokers. Additionally, 42.2% had hypertension, 6.3% had coronary heart disease, and 19.5% had Type-II diabetes mellitus. Biliary atresia was present in 3.1% of participants, while 8.6% had hepatitis. 26.6% had high cholesterol levels, and 57% had a history of malignancy. Soft drink consumption was reported by 49.2%, while 39.8% consumed fast food. Conclusion: Most of the participants were non-alcoholic, non-smokers, and free from chronic diseases, a significant portion had female gender, age above 40, from urban area, history of previous surgery, consumed soft drinks, and followed high-protein diets which was risk factors for cholelithiasis. So implement health education programs targeting the community to raise awareness about the risk factors associated with cholelithiasis